(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study was conducted to confirm the effect of applying flipped learning to simulation training of nursing students. Methods/Statistical analysis: The study was the experiment with pre and post design in single group. The subjects of this study were 88 nursing students who were taking the simulation training course of nursing college. The learning model was designed with a total of 11 programs based on the ‘PRTNER’ model. Collected data were analyzed using descriptive statistics and paired t-test using SPSS 22.0. Findings: Although there was no statistically significant difference in the problem solving ability(t=-1.342, p=.183) between before and after applying flipped learning to simulation training, the significant improvement was achieved in self-directed learning ability(t=-2.187, p=.031), communication ability(t=-5.316, p<.001), and satisfaction of instruction(t=-2.830, p=.006). Therefore, using the teaching and learning method with flipped learning, the learning outcomes can be maximized by improving the core competencies that nursing students should have. These results are useful as basic data for the development of teaching and learning methods that can improve the core competencies of nursing students. Improvements/Applications: Based on this results, we propose the follow-up study to confirm the effectiveness of various teaching and learning methods applying flipped learning to the theoretical curriculum in nursing science.s